Principal results of the studies carried out at the Instituto de Ciencia Animal on bovine milk production - Reyes, Julio J. (Cuban Journal of Agricultural Science, 2016)
The main results obtained in milk production under Cuban conditions, with the grass as basic foods are shown. With the appropriate interaction of stocking rate and grass varieties, dairy productions between 8 and 9 kg d-1 during the rainy season were reached, with stocking rate of 3.0 cows ha-1 in coast cross Bermuda grass (Cynodon dactylon), 4.0 cows ha-1 in pangola grass (Digitaria decumbens Stent) and 5.0 cows ha-1 in star grass (Cynodon nlemfuensis).For the grass rotational management, the number of paddocks per group was between four and eight. The application of the pin pointer method and followers make possible higher balance between the composition and grass quantity and the animals requirements. With the use of legumes in the system, productions of 15 kg milk cow-1 d-1 can reached, with the lower supplement use. The supplementation showed higher advantage when the differential between the grass and the animal potential was more marked. The supplementation effect was higher at the beginning of lactation. The feeding systems with restricted grazing in the dry season, complemented with silage or sugar cane as forage, reached individuals productions between 7 and 8 kg of milk d-1, with complement intake between 5.8 and 7.3 kg DM cow -1 d-1for sugar cane and silage, respectively. Key words: grazing, grasses, legumes, supplementation, milk, quality